1996
DOI: 10.1104/pp.110.2.689
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Nitrogen Limitation on Photosynthetic Efficiency of Photosystems I and II in Microalgae

Abstract: The effects of nitrogen starvation on photosynthetic efficiency were examined in three unicellular algae by measuring changes in the quantum yield of fluorescence with a pump-and-probe method and thermal efficiency (i.e. the percentage of trapped energy stored photochemically) with a pulsed photoacoustic method together with the inhibitor 3-(3,4-dichlorophenyl)-l,l-dimethylurea to distinguish photosystems I and II (PSI and PSII). Measured at 620 nm, maximum thermal efficiency for both photosystems was 32% for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
141
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(163 citation statements)
references
References 22 publications
18
141
3
1
Order By: Relevance
“…Previous indirect determinations from F 730 and a chl spectra have shown that cyanobacteria have the lowest proportion of total light absorption by PSII (Johnsen and Sakshaug 1996;Lutz et al 2001). Berges et al (1996) measured the effective absorption and concentration of reaction centers for both PSI and PSII in T. weissfloggii under nutrient replete growth conditions and demonstrated that 46% of total absorption was from photosynthetic pigments associated with PSII. This value is very similar to the value that we report for T. weissflogii.…”
Section: Figmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous indirect determinations from F 730 and a chl spectra have shown that cyanobacteria have the lowest proportion of total light absorption by PSII (Johnsen and Sakshaug 1996;Lutz et al 2001). Berges et al (1996) measured the effective absorption and concentration of reaction centers for both PSI and PSII in T. weissfloggii under nutrient replete growth conditions and demonstrated that 46% of total absorption was from photosynthetic pigments associated with PSII. This value is very similar to the value that we report for T. weissflogii.…”
Section: Figmentioning
confidence: 99%
“…Compared to eukaryotic phytoplankton, cyanobacteria have a high n PSII (Barlow and Alberte 1985) and much lower ratios of PSII to PSI (Barlow and Aberte 1985;Berges et al 1996;Falkowski and Raven 1997). In addition, most chlorophyll a is associated with PSI.…”
Section: Hl:d Tertiolecta Ll (ٗ) and P Minimum Hl:e Huxleyi Ll (᭞)mentioning
confidence: 99%
See 3 more Smart Citations